Cardiac autonomic neuropathy may play a role in pathogenesis of atherosclerosis in type 1 diabetes mellitus. (December 2017) - Mala, Sarka; Potockova, Veronika; Hoskovcova, Lucie; Pithova, Pavlina; Brabec, Marek; Kulhankova, Jaroslava; Keil, Radan; Riedlbauchova, Lucie; Broz, Jan
Highlights: The relationship of subclinical atherosclerosis and autonomic neuropathy was studied. Diabetic autonomic neuropathy is associated with higher intima media thickness. Diabetic autonomic neuropathy may play a role in pathogenesis of atherosclerosis. Abstract: Aims: Cardiac autonomic neuropathy (CAN) is a frequent and severe complication of type 1 diabetes mellitus (T1DM). CAN diagnosis is associated with increased cardiovascular morbidity and mortality, often due to progressive atherosclerosis. Carotid intima media thickness (CIMT) is a surrogate marker of the atherosclerosis. The aim of our study was to evaluate the relationship between CIMT and CAN in T1DM patients. Methods: Total of 49 T1DM patients and 45 healthy controls were examined for CAN presence and CIMT. CAN was diagnosed based on the results of Ewing test battery and spectral analysis of heart rate variability. CIMT was measured by two-dimensional ultrasound. Biochemical, anthropometric and anamnestic risk markers of atherosclerosis were evaluated. We used logistic types of generalized additive models (GAM) for statistical analysis. Results: CAN was detected in 22 out of 49 T1DM patients (45%). All 45 healthy controls had normal cardiovascular autonomic tests results. CIMT was significantly positively associated with T1DM diagnosis (p = 0.0251), CAN diagnosis (p = 0.007), age (p < 0.0001), BMI (p = 0.0435) and systolic blood pressure (p = 0.0098). CAN effect on CIMT interacted with the effect of T1DM. The combination of both factors significantly increased CIMT more than the sum of the individual T1DM and CAN status. Conclusions: CAN is significantly associated with higher CIMT in T1DM patients. CAN may play a role in pathogenesis of atherosclerosis in type 1 diabetes mellitus.